Global, regional, national burden of colorectal cancer from 1990 to 2021, with projections of incidence to 2050: a systematic analysis of the global burden of disease study 2021 - Chang, Shiyu; Chang, Yu; Li, Fan; Xu, Zifeng; Han, Xiaoping; Liu, Yue; Li, Hongyan; Hu, Sileng; Tang, Tongyu (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a common malignant tumor of the digestive system, characterized by a high incidence and mortality rate. This study aimed to investigate the epidemiological characteristics of CRC between 1990 and 2021.MethodsData on CRC were obtained from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2021. We focused on the effects of age, sex, risk factors, and the socio-demographic index (SDI) on the burden of CRC. Estimated annual percentage changes (EAPCs) were calculated to evaluate changes in the age-standardized rate (ASR) of incidence, mortality and DALYs, as well as their trends in CRC burden. Frontier and health inequality analyses assessed health management potential and disease burden by country, while the Bayesian age-period-cohort (BAPC) model predicted CRC incidence patterns by age group through 2050.FindingsGlobal ASMR and ASDR declined, but ASIR rose overall (EAPC = 0.15), with significant gender disparities (male EAPC = 0.50 vs. female EAPC=-0.29). Middle SDI regions saw the steepest ASIR increase (EAPC = 1.38). In 2021, Australasia had the highest ASIR, while East Asia had elevated ASIR and ASMR. CRC burden predominantly affected ages 60–79. Dietary risks surpassed metabolic, environmental, and behavioral factors as the leading contributor to CRC burden. Frontier analysis revealed that 15 countries with the longest effective distances (indicating suboptimal health outcomes) were predominantly high-SDI nations (SDI >0.70). Projections suggest persistently high global ASIR through 2050, particularly among ages 70–74.InterpretationCRC burden varies by gender, age, and region. While some regions show declining mortality, overall burden remains substantial, especially in middle/low-middle SDI areas. Notably, even high-SDI countries exhibit significant gaps in CRC management. Targeted public health strategies—optimizing prevention, early detection, and resource allocation—are critical to address rising incidence and disparities.